Media Promosi Kesehatan Ular Tangga VS Leaflet ASI Eksklusif terhadap Pengetahuan dan Kesiapan Ibu Menyusui - Linda Puji Astutik; Herlinadiyaningsih Herlinadiyaningsih (Poltekkes Kemenkes Palu, 2023)
Introduction: Currently exclusive breastfeeding promotion media uses written media such as leaflets, whereas snake and ladder promotion media are easier to digest and more interesting so that it is expected to increase the knowledge and readiness of exclusively breastfeeding mothers. Objectives: to measure the difference in the effect of exclusive breastfeeding version of the snake and ladder health promotion media with leaflets on the knowledge and readiness of mothers in exclusive breastfeeding. Methods: This study used a quasi-experimental pretest posttest design on 70 pregnant women in the third trimester from March to June 2022. The analysis used frequency distribution, Wilcoxon test and unpaired T test. Result: the average knowledge (9.1) and readiness (14.7) of the group with snakes and ladders media was higher than the knowledge (6.1) and readiness (12.1) group with leaflet media with p=0.000 (<0.05) Conclusion: the effect of health promotion media using exclusive breastfeeding version of snake and ladder is better than exclusive breastfeeding leaflet on mother's knowledge and readiness regarding exclusive breastfeeding. Thus, it is recommended that the exclusive breastfeeding version of the snake and ladder health promotion media should be used instead of leaflets.